2015 Tyrrhenian International Workshop on Digital Communications (TIWDC) 2015
DOI: 10.1109/tiwdc.2015.7323333
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength division multiplexed optical eigenvalue modulated system

Abstract: Wavelength division multiplexing is essential for achieving large capacity optical fiber transmission for any kind of modulation format. In this paper, we propose a wavelength division multiplexed optical eigenvalue modulated system and discuss its advantages and remaining issues for practical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…has been used by the Osaka group and co-authors [66][67][68][69][70][71][72]. Within this method the ZSP solution components v 1,2 are expanded in the Fourier series and the ZSP itself is reformulated as an eigenvalue problem in the Fourier space [43,45].…”
Section: Fourier Collocation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…has been used by the Osaka group and co-authors [66][67][68][69][70][71][72]. Within this method the ZSP solution components v 1,2 are expanded in the Fourier series and the ZSP itself is reformulated as an eigenvalue problem in the Fourier space [43,45].…”
Section: Fourier Collocation Methodsmentioning
confidence: 99%
“…As a result, so far the NFTbased DBP approach was elaborated only for the soliton-free case [50,73]. For the third design, which is referred to as the "hybrid method", information is encoded in the time domain but the detection stage involves NFT operations and decision is made using NF spectrum data [62,63,66,67,70].…”
Section: Nft For Optical Communicationsmentioning
confidence: 99%
“…However, it was observed that spectral broadening can be a limiting issue. In a number of other works general communication system designs, including the modulation on the norming constants, were studied [63][64][65][66][67][68][69][70]. Recently in [71], transmission of 6 bits/symbol at 24 Gbps over 1000 km of fibre was demonstrated by experiment using a single eigenvalue and its corresponding norming constant.…”
Section: Related Workmentioning
confidence: 99%